Parents' Attitude Toward Child Abuse Conducted in the Health Centers of Tabriz - Maliheh Asadollahi; Mahnaz Jabraeili; Mohammad Asghari Jafarabadi; Marzieh Hallaj (Shiraz University of Medical Sciences, 2016)
Background: Attitudes are very important in the formation of behaviors. Parents' attitudes toward children and behaviors with them are the main causes of child abuse. Identifying these attitudes and their related factors can be the primary basic action for prevention of child abuse. Objectives: This study was conducted to investigate the parents' attitudes toward child abuse in the health centers of Tabriz. Patients and Methods: In this cross-sectional study 384 parents with children 2 to 12 years old, filled a questionnaire about parents' attitude toward child abuse in the 13 health centers of Tabriz. Data was analyzed using SPSS (version 16.0). Results: The results showed that the mean score of total attitude toward child abuse was significantly higher than the middle (P < 0.001) and was correlated significantly with 'parents' educational level, number of children they have, attendance status and economic status (P < 0.05). Conclusions: The results showed that the parents' attitudes toward child abuse were negative, but because of the relationship between parents' attitudes with some of their demographic characteristics, parents should be supported economically and socially to prevention of child abuse.